IMPLEMENTATION OF CONSERVATION REGENARATION IN HIGHER EDUCATION - Rahmaningtyas, Wisudani; Purasani, Hana Netti; Tusyanah, Tusyanah (Universitas Pendidikan Indonesia, 2018)
The purpose of this study is to analyze the application of conservation regeneration in the Faculty of Economics, Universitas Negeri Semarang (UNNES). The research method used is mix method (combination method). The changes observed or measured are conservation regeneration in the Faculty of Economics. Data collection techniques used observation, documentation, interviews and questionnaires. Data analysis uses interactive analysis and descriptive analysis. The results showed that the level of student knowledge of Rector Regulation No. 22 of 2009 are 42,59% just know, 46,29% do not know and 11,11% already read. Interviews and observations indicate that students have not fully implemented conservation cadre on campus grounds. Some students still throw garbage out of place, smoke in campus areas and are inefficient in energy use.